2011
DOI: 10.1186/1472-6882-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid partly antagonizes resveratrol mediated heme oxygenase-1 but not paraoxonase-1 induction in cultured hepatocytes - role of the redox-regulated transcription factor Nrf2

Abstract: BackgroundBoth resveratrol and vitamin C (ascorbic acid) are frequently used in complementary and alternative medicine. However, little is known about the underlying mechanisms for potential health benefits of resveratrol and its interactions with ascorbic acid.MethodsThe antioxidant enzymes heme oxygenase-1 and paraoxonase-1 were analysed for their mRNA and protein levels in HUH7 liver cells treated with 10 and 25 μmol/l resveratrol in the absence and presence of 100 and 1000 μmol/l ascorbic acid. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 38 publications
4
102
1
1
Order By: Relevance
“…Rocha et al (2009) showed higher activity of SOD, catalase or superoxide dismutase in liver of rats fed a high fat diet in presence of RSV (1 mg · kg -1 body weight per day). It was also reported that RSV in human hepatoma cells (HUH7) and in rats induces the HO-1 enzyme (Wagner et al, 2011). This was not confirmed in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…Rocha et al (2009) showed higher activity of SOD, catalase or superoxide dismutase in liver of rats fed a high fat diet in presence of RSV (1 mg · kg -1 body weight per day). It was also reported that RSV in human hepatoma cells (HUH7) and in rats induces the HO-1 enzyme (Wagner et al, 2011). This was not confirmed in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…However, this approach is questionable because of the experimental observation that exogenous supplement antioxidants, such as vitamin C, do not generate effective and consistent results for the control of glucose level and diabetic complications [81][82][83] . A potential problem of longterm vitamin C administration with its suppressing effect on the endogenous Nrf2 system [84] , therefore, is unable to produce sufficient antioxidant function. The utilization of Nrf2 activator may provide additional advantages compared with external antioxidant intake to treat oxidative stress and prove the effectiveness of this strategy [81] .…”
Section: Nrf2 System As a Potential Drug Target For Diabetes Treatmentmentioning
confidence: 99%
“…In addition to extracellular matrix (ECM) synthesis, AA regulates the differentiation of multi-potent precursor cells into bone cells by stimulation of integrin signalling and supporting cell matrix interaction [20]. The use of AA as an inducer of osteoblast differentiation would be an advantage in the treatment of bone-related diseases [21]. Dexamethasone (DM) is a synthetic steroidal anti-inflammatory drug which has been shown to induce osteogenic differentiation of MSCs in combination with ascorbate-2-phosphate and β-glycerophosphate [22].…”
Section: Introductionmentioning
confidence: 99%